The Amakusa Edition of Álvares’ Grammar (1594): Sources and Innovation - Assunção, Carlos; Toyoshima, Masayuki (Onomázein, 2018)
Amongst all the editions of Álvares’ grammar, the Amakusa edition (1594) merits special attention, not only for being the first grammatical treatise to mention Japanese verbal paradigms in print, but for being the first adaptation of the Jesuit grammar outside of Europe, having been created in a well-defined missionary context. Using contrastive analysis with the Lisbon Edition (1573), it can be concluded that this was the grammar that served as the basis for drawing up the Amakusa grammar, which has some unique features such as being the first to be published in printed form in the East, in the context of increasing numbers of students in Japanese Jesuits schools.